2015
DOI: 10.1097/opx.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Eye Examination Testability in Children with Autism and in Typical Peers

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…We sought help from the teachers or parents whenever required to successfully complete the assessment in some of the children. Our finding is in accordance with a study done by Coulter et al 12 in determining the testability of vision tests in children with autism. We agree with their view that children with ID can perform most of the vision tests if appropriate visual, communicative and sensory supports are incorporated in the testing protocol.…”
Section: Discussionsupporting
confidence: 94%
“…We sought help from the teachers or parents whenever required to successfully complete the assessment in some of the children. Our finding is in accordance with a study done by Coulter et al 12 in determining the testability of vision tests in children with autism. We agree with their view that children with ID can perform most of the vision tests if appropriate visual, communicative and sensory supports are incorporated in the testing protocol.…”
Section: Discussionsupporting
confidence: 94%
“…A video illustrating the test also helped to prepare individuals for their involvement. The high success rates found in this study support the recent work of Coulter et al (2015) who report that with appropriate preparation individuals with ASD can successfully participate with vision assessments.…”
Section: Discussionsupporting
confidence: 92%
“…Having straightforward written information about what occurs during an eye test, and offering the opportunity for open days and familiarisation visits at quiet times can help prepare the individual and family. Coulter et al reported strategies to encourage good testability of vision in ASD, highlighting that quiet‐time appointments, consistency of clinicians, and preparation using social stories help prepare the child for vision tests promoting a positive experience. However, every individual with ASD is different, and it is important to develop a flexible approach to best support their needs.…”
Section: Discussionmentioning
confidence: 99%